Instructional Material Design of Project-Based Learning to Train Creative Thinking Skills in Society 5.0 Era - Rabia, Supriyati Fatma; Asrul, Asrul; Genç, Nurbaiti Elita; Azizah, M.A.N. (Profesi Pendidikan Dasar, 2024)
It is hoped that the use of creative and environmentally relevant instructional material will be able to improve creative thinking skills, among others. The aim of this research is to determine the influence of students creative thinking skills using the project-based learning. This research is a type of quasi-experimental research. The design in this study used a two-group pretest-posttest design. The population of this study was all second-semester students, consisting of 5 classes with a total of 153 students. The research sample consisted of two classes, namely the experimental class and the control class which was taken using cluster random sampling, the total sample was 70 students. This research instrument is a project-based creative thinking skills test in the form of an essay test which is in accordance with aspects of creative thinking skills. The data analysis used is the t-test. The results of this research show that there is an influence of project-based learning-based instructional material with the characteristics of Papuan local wisdom and an increase in students' creative thinking skills per aspect in the medium category.